Gut–Brain Axis and Mood Disorder - Liu, Lu; Zhu, Gang (Frontiers in Psychiatry, 2018)
Humans have over 100 trillion bacteria, highly abundant in the intestinal tract. Evidence suggests that intestinal microbiota is associated with the neuro-endocrine-immune pathways and can be associated with various mood disorders. This review summarizes findings from studies looking into neurobiochemical, neuroendocrine, and neuroimmune system mechanisms of the gut–brain axis to determine the relationship between intestinal microbiota and mood disorders. The effect of prebiotics, probiotics and antibiotics on mood disorders are also discussed, with the aim to propose some new therapeutic strategies for mood disorders.